Serum melatonin level and oxidative stress in sickle cell anemia - Tomimatsu Shimauti, Eliana Litsuko [UNESP]; Humberto Silva, Danilo Grunig [UNESP]; de Almeida, Eduardo Alves [UNESP]; Antoniazzo Zamaro, Paula Juliana [UNESP]; Belini Junior, Edis [UNESP]; Bonini-Domingos, Claudia Regina [UNESP] (Academic Press Inc. Elsevier B.V., 2010)
This study evaluated serum melatonin levels in patients with sickle cell anemia (SCA) and compared the results to lipid peroxidation by determining thiobarbituric acid-reactive substances (TBARS) and Trolox equivalent antioxidant capacity (TEAC). The group studied was composed of 15 SCA patients and 24 subjects without hemoglobinopathies. The average melatonin level was significantly reduced in the SCA patients (p<0.001) when compared to the control group. The SCA patients showed significantly higher values for TBARS and TEAC when compared to values obtained for the control group (p<0.001 and p<0.01). Results from the correlation analysis in the SCA group were not statistically significant for any parameters except for TBARS and TEAC levels, which had a positive correlation (r = 0.51; p = 0.04), suggesting the participation of melatonin in antioxidant defense. The use of melatonin could be a possible therapeutic target for improving antioxidant defense and to reduce oxidative damage, alleviating symptoms associated with SCA. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Sickle cell anemia; Antioxidant capacity; Melatonin